تحليل الأخطاءالنحوية في مقدمة خطبة الجمعة (دراسة السياقية) - aziz alkhumairi (UIN Fatmawati Sukarno Bengkulu, 2019)
ABSTRACT This research is a continuation of the research that has been done before, except that the theme carried out in this study is different. The aim is that more and more references to research in this theme will be the lower level of difficulty of Non-Arabic speakers in speaking Arabic, especially the mistakes of Nahwu (Syntacs). Determination of location became important in this study, researchers took boarding school respondents in the city of Bengkulu who excelled in terms of Arabic, namely Darussalam Islamic Boarding School located in the City of Bengkulu. The approach used is qualitative and the data are like numbers to reinforce conclusions. His method is descriptive analysis, by describing all data with explanations in the form of words. The method of data collection is by interviewing, unstructured dialogue, and recording using audio media. The results showed that there were 56 conversational errors in Scientific Sermon activities, there were 38 syntactic errors, meaning that around 68% specific language errors occurred in syntax, while the cause of errors was focused on 3 big points, first: Speakers underestimated rules, the error rate was 18% second: Speakers do not know the rules, the rate of occurrence of errors is 34%, third: Interverence rate of occurrence of errors is 18%.